Improvement of antimicrobial activity of Pediococcus pentosaceus strain 2397 in suppressing Escherichia coli - EMMA RIFTYAN; YUSMARINI YUSMARINI; EVY ROSSI; USMAN PATO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Riftyan E, Yusmarini, Rossi E, Pato U. 2024. Improvement of antimicrobial activity of Pediococcus pentosaceus strain 2397 in suppressing Escherichia coli. Biodiversitas 25: 2500-2506. Lactic acid bacteria exhibit antibacterial activity that suppresses spoilage and pathogenic bacteria. Due to their antagonistic action against foodborne pathogens such as Escherichia coli, LAB isolated from dairy products have attracted considerable attention as a potential food preservative. Furthermore, bioactive compounds generated by forming LAB biofilms may exhibit efficacy against pathogenic microorganisms and their toxin. Combining LAB biofilms and other LAB products, such as bacteriocins, could offer a significant method against pathogenic microorganisms and their biofilms. The aim of this study was to evaluate the effects of optimization of media composition and incubation conditions on the antimicrobial activities of cell-free supernatant (CFS) from Pediococcus pentosaceus strain 2397 to inhibit E. coli FNCC-19. The antimicrobial activity of CFS was determined using agar well diffusion method. The results revealed that antimicrobial activity of P. pentosaceus strain 2397 was enhanced by optimizing the media composition and incubation conditions. Pediococcus pentosaceus strain 2397 exhibited excellent antimicrobial activity against E. coli. In MRS, 5% (v/v) of P. pentosaceus strain 2397+2.0% (w/v) yeast extract with pH 7.0 showed an inhibition zone of 10.44 mm. Therefore, strain 2397 may be effective in producing bacteriocin as a preservative for food products.